Posted by Samantha on Tuesday, November 4, 2008 at 8:05pm.
y = e^2xsin3x Find the derivative.
So I used the product rule and I got sin3x(e^2x)+cos^3x(e^2x). But the actual answer is sin3x(2e^2x)+cos^3x(3e^2x) Where the the 2 and 3 before the e come from?

Calculus part 3 so sorry  Damon, Tuesday, November 4, 2008 at 8:55pm
I guess you mean
[e^(2x)]sin 3x
sin 3x [2 e^(2x)] + 3 cos (3x) e^(2x)
hey same mistake as earlier
d/dx (e^u) = du/dx * e^u
and
d/dx (sin u) = du/dx cos u
if u = 2x, then du/dx = 2
if u = 3x, then du/dx = 3